Pragmatic Based Learning of Indonesian Speaking Skills at Muslim Santitham Foundation School Thailand - Oktavia Winda Lestari; Mohamad Jazeri (Pedagogy Review, 2024)
Abstract: This article aims to examine the preconceptions in the dialogue of learning pragmatic-based Indonesian speaking skills at Muslim Santitham Foundation School Thailand. Data were obtained from pragmatic-based Indonesian learning activities at Muslim Santitham Foundation School Thailand. Data was collected by observation and documentation techniques. Observation was used to determine the strategies and learning models of Indonesian speaking skills in pragmatic-based dialogue. Documentation is used to obtain data from pragmatic-based learning. This research is a qualitative research with a pragmatic approach, namely the study of language used in real interactions that cannot be separated from the context. The data was analyzed with an interactive model adapted from Miles and Huberman, namely data collection, data reduction, data presentation, verification, and final conclusion. The results of the data analysis found that there were six types of preconceptions in the dialogue of learning Indonesian speaking skills. The data consisted of existential presumption, factual presumption, lexical presumption, structural presumption, nonfactual presumption, and counterfactual presumption.   Keywords: learning, speaking skills, pragmatics, preconceptions.